2022
DOI: 10.1155/2022/2016441
|View full text |Cite
|
Sign up to set email alerts
|

Development Trend Prediction of Chengdu Plain Economic Zone Based on Multiple Linear Regression Grey Correlation Degree

Abstract: Urban agglomeration is the mainstream trend of urban development in the world. It is also the main form of new urbanization in China and an important platform to participate in international competition and cooperation. The pattern of industrial division of labor has basically taken shape in Chengdu Plain Economic Zone, and the industrial cooperation system has been gradually established. However, the phenomenon of industrial isomorphism is still prominent. In the process of promoting coordinated industrial de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Linear regression is the main empirical tool in economics, and numerous studies have reported the significance of linear regression models (74)(75)(76)(77). Using regression models, this study confirms the connection between low-carbon economic development, health, the growth of the economy, and the emitting of carbon, and sectors.…”
Section: Model Formulationsupporting
confidence: 74%
“…Linear regression is the main empirical tool in economics, and numerous studies have reported the significance of linear regression models (74)(75)(76)(77). Using regression models, this study confirms the connection between low-carbon economic development, health, the growth of the economy, and the emitting of carbon, and sectors.…”
Section: Model Formulationsupporting
confidence: 74%
“…The second method uses statistical models to predict PM 2.5 concentration. In 2021, Xu Dong et al [17] used the basic monitoring index data on temperature, inhalable particulate matter PM 10 , and CO in Chengdu as the research object, and built a multivariate linear regression (MLR) model for PM 2.5 concentration. In the same year, Xu Yixin et al [18] combined a wavelet analysis with a regression model, and used the W-MLR model to analyze PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%